Biomimicry of Blue Morpho butterfly wings: An introduction to nanotechnology through an interdisciplinary science education module. Issue 11 (14th July 2021) - Kirya, Paula; Chen, Eric; Achterman, Marina; Eugenio, Kelli; Beshir, Zekaria; Ngoy, Natalie; Siddique, Radwanul Hasan; Cakmak, Atilla Ozgur; Ashcroft, Jared
Abstract: Biomimicry is the practice of imitating naturally occurring bio‐designs through engineering and invention. For instance, Blue Morpho butterfly wing colors are a result of the reflection and refraction of nanostructures embedded in the wing and have inspired practical applications in nanofabrication and photonics. Interdisciplinary science educational materials have been developed that demonstrate the cross‐disciplinary aspects and biomimetic properties used in designing nano‐based devices. The unique optical properties of the Blue Morpho wing provides an excellent source of demonstrating how aspects of chemistry, biology, physics, and nanotechnology relate. Specifically, these educational tools demonstrate concepts including natural selection, chemical and physical properties, structure at the nanoscale, optical, and electromagnetic design. In addition, the engaging activities are correlated to how nanotechnology drives invention and provides students a mechanism to be introduced to the possibilities nanotechnology provides. A comprehensive combination of lab, cleanroom, and classroom activities are suggested to promote remote learning. Abstract : Biomimicry is the practice of imitating naturally occurring bio‐designs through engineering and invention. Interdisciplinary science educational materials have been developed to demonstrate the cross‐disciplinary aspects and biomimetic properties used in designing nano‐based devices. The unique optical properties of the Blue Morpho wing provides an excellent source of demonstrating how aspects of chemistry, biology, physics, and nanotechnology relate.